In this issue - Yamakawa T, Peter (2015)
We would like to introduce the 39th issue of the Journal of Economics, Finance and Administrative Science (JEFAS). The Journal is indexed to the most prestigious databases worldwide like Scopus, Social Science Citation Index (SSCI), Redalyc, EconLit and Gale. This issue has six papers, as usual, and one extra article in a section called Doctoral Dissertation which discusses a recent doctoral student’s research in a Peruvian sample. The first article, “Emerging Markets Integration in Latin America (MILA) Stock market indicators: Chile, Colombia, and Peru”, is an empirical paper that estimates the impact of the Latin American Integrated Market (MILA) start-up in the main indicators of the countries’ stock markets that conform the MILA group. Doi: http://dx.doi.org/10.1016/j.jefas.2015.10.003